2023
DOI: 10.3389/fnagi.2023.1153496
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain networks and connections in chronic heart failure patients complicated with cognitive impairment

Abstract: ObjectiveAccumulating evidence shows that cognitive impairment (CI) in chronic heart failure (CHF) patients is related to brain network dysfunction. This study investigated brain network structure and rich-club organization in chronic heart failure patients with cognitive impairment based on graph analysis of diffusion tensor imaging data.MethodsThe brain structure networks of 30 CHF patients without CI and 30 CHF patients with CI were constructed. Using graph theory analysis and rich-club analysis, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The “heart-brain axis” refers to the bidirectional communication network between the heart and the central nervous system (CNS), involving hemodynamic changes and neuronal signaling. This concept involves a tight heart-brain feedback interaction and is highly complex ( 11 , 12 ). Researches have demonstrated that more than 50% of patients with CHF experience secondary brain damage, which can manifest as autonomic damage, cognitive dysfunction, and neuropsychological deficits ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The “heart-brain axis” refers to the bidirectional communication network between the heart and the central nervous system (CNS), involving hemodynamic changes and neuronal signaling. This concept involves a tight heart-brain feedback interaction and is highly complex ( 11 , 12 ). Researches have demonstrated that more than 50% of patients with CHF experience secondary brain damage, which can manifest as autonomic damage, cognitive dysfunction, and neuropsychological deficits ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a functional MRI technique that demonstrates the direction and speed of water molecule diffusion in biological tissues [ 20 ]. DTI can provide both mean diffusivity (MD) and fractional anisotropy (FA) values, which might reflect the structure and organization of complex tissues such as the brain, heart, prostate, kidney, liver, and breast [ 21 , 22 , 23 , 24 ]. Recent studies have reported that the quantitative parameter values of DTI are useful to differentiate the testes of NOA patients from controls and the testes of infertile men with varicocele from controls [ 18 , 25 ].…”
Section: Introductionmentioning
confidence: 99%